2013
DOI: 10.1371/journal.pone.0069415
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxy Hexenal Derived from Docosahexaenoic Acid Protects Endothelial Cells via Nrf2 Activation

Abstract: Recent studies have proposed that n-3 polyunsaturated fatty acids (n-3 PUFAs) have direct antioxidant and anti-inflammatory effects in vascular tissue, explaining their cardioprotective effects. However, the molecular mechanisms are not yet fully understood. We tested whether n-3 PUFAs showed antioxidant activity through the activation of nuclear factor erythroid 2-related factor 2 (Nrf2), a master transcriptional factor for antioxidant genes. C57BL/6 or Nrf2−/− mice were fed a fish-oil diet for 3 weeks. Fish-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 51 publications
8
75
1
5
Order By: Relevance
“…On the other hand, treatment of the EA.hy926 cell line with 100 μM DHA for various times dramatically enhanced Nrf2 nuclear protein expression (Figure 7C), consistent with a previous report [42]. DHA-induced Nrf2 nuclear translocation and HO-1 gene transcription was also reported in human umbilical vein endothelial cells (HUVEC) [43]. …”
Section: Resultssupporting
confidence: 90%
“…On the other hand, treatment of the EA.hy926 cell line with 100 μM DHA for various times dramatically enhanced Nrf2 nuclear protein expression (Figure 7C), consistent with a previous report [42]. DHA-induced Nrf2 nuclear translocation and HO-1 gene transcription was also reported in human umbilical vein endothelial cells (HUVEC) [43]. …”
Section: Resultssupporting
confidence: 90%
“…Furthermore, we identified the preventive effects of ω‐3 PUFAs against the oxidative stress‐induced cell death. The present findings are consistent with recent studies suggesting that the anti‐oxidant effects are induced by ω‐3 PUFAs in HUVECs and 3T3‐L1 adipocytes. ω‐3 PUFAs suppress inflammatory responses by inhibiting the arachidonate cascade in neutrophils, and the stimulation of the G protein‐coupled receptor 120 by DHA exerts anti‐inflammatory effects in macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…ω‐3 PUFAs suppress inflammatory responses by inhibiting the arachidonate cascade in neutrophils, and the stimulation of the G protein‐coupled receptor 120 by DHA exerts anti‐inflammatory effects in macrophages. Recent studies report the anti‐oxidant effects of 4‐hydroxy‐2‐hexanal (4‐HHE), resolvin E1 and protectin D1, which are intracellular metabolites of ω‐3 PUFAs. We also examined the effects of 4‐HHE on the mRNA levels of anti‐oxidant enzymes and found that 4‐HHE increased the mRNA levels of Ho‐1 , Nqo‐1 and Cat (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…Once oxidation reached a threshold level, the free radical chain reaction of lipid peroxidation might have exceeded the protection supplied by DHA, leading to pro-oxidant effects. In agreement with our results on 4-HHE, Ishikado et al[120] recently reported that supplementation with dietary fish oil led to increased HHE aortic concentrations and increased the expression of the antioxidant enzyme heme oxygenase-1, and endotheliumdependent vasodilatation. As reviewed very recently[121], potential molecular mechanisms to explain the antioxidant effects of omega-3 fatty acids would be the quenching of ROS as well as direct inhibition of NADPH oxidase 4 (Nox-4) by DHA[122].…”
supporting
confidence: 93%